2000
DOI: 10.1046/j.1471-4159.2000.0750091.x
|View full text |Cite
|
Sign up to set email alerts
|

The Transcription Factor E2F1 Modulates Apoptosis of Neurons

Abstract: Abstract:The transcription factor E2F1 is known to mediate apoptosis in isolated quiescent and postmitotic cardiac myocytes, and its absence decreases the size of brain infarction following cerebral ischemia. To demonstrate directly that E2F1 modulates neuronal apoptosis, we used cultured cortical neurons to show a temporal association of the transcription and expression of E2F1 in neurons with increased neuronal apoptosis. Cortical neurons lacking E2F1 expression (derived from E2F1 Ϫ/Ϫ mice) were resistant to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
85
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(92 citation statements)
references
References 62 publications
6
85
1
Order By: Relevance
“…E2F1 is thought to promote the exit from G 0 phase (34), and its overexpression induces apoptosis in quiescent cells (35) and postmitotic neurons (26,36). We found that E2F1 abrogated necdin-induced growth arrest and morphological differentiation of N1E-115 cells (Figs.…”
Section: E2f1 Abrogates Necdin-induced Growth Arrest Of N1e-115 Cellsmentioning
confidence: 67%
“…E2F1 is thought to promote the exit from G 0 phase (34), and its overexpression induces apoptosis in quiescent cells (35) and postmitotic neurons (26,36). We found that E2F1 abrogated necdin-induced growth arrest and morphological differentiation of N1E-115 cells (Figs.…”
Section: E2f1 Abrogates Necdin-induced Growth Arrest Of N1e-115 Cellsmentioning
confidence: 67%
“…E2F1 is upregulated in neurons subjected to apoptotic stimuli in vitro 46,68,104,105,107,109 and in vivo 37 and is elevated in degenerating neurons of patients with Alzheimer disease and with Down's syndrome. 93,110 In addition, neurons treated with an E2F1 antisense 68,104 as well as neurons cultured from mice null for E2F1 107,109,[111][112][113] are at least partially protected from diverse apoptotic stimuli. Although such data can be taken to support a mechanism of E2F1-dependent gene activation, here again an alternative interpretation is possible.…”
Section: Does E2f-dependent Gene Activation Have a Role In Neuron Death?mentioning
confidence: 99%
“…Apoptotic stimuli induce Rb phosphorylation through activation of cyclin-dependent kinases to activate E2F1 in neurons Hou et al, 2002). In addition, forced expression of E2F1 in postmitotic neurons using viral vectors induces apoptosis (Azuma-Hara et al, 1999;Hou et al, 2000;O'Hare et al, 2000). These findings suggest that the regulation of E2F1 activity is crucial for the control of neuronal apoptosis.…”
Section: Introductionmentioning
confidence: 96%